Pengaruh Keragaman Produk Dan Kualitas Produk Terhadap Loyalitas Pelanggan Di Mata Hati Cafe Kediri - Evrina Latando Putri (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2023)
Intense competition in the culinary world forces entrepreneurs to think about what consumers want, including product diversity and product quality. Researchers chose Mata Hati Cafe because it was based on existing considerations. The aim of the research is to partially and simultaneously explain the influence of Product Diversity (X1) and Product Quality (X2) on Customer Loyalty (Y) at Mata Hati Cafe Kediri. This research uses quantitative methods, in order to find out how much influence these variables have on customer loyalty. The population was 5,329 customers using non-probability sampling techniques with a purposive sampling approach. Data collection techniques used observation, interviews, questionnaires and literature study. Samples were taken from 98 respondents using the Slovin formula. The analysis techniques used are validity test, reliability test, classical assumption test, multiple linear regression test, t test, F test, and coefficient of determination test. Data processing with the SPSS program. The results of this research show that product diversity sometimes has a significant influence on customer loyalty at Mata HatiCafe Kediri, product quality sometimes has a significant influence on customer loyalty at Mata HatiCafe Kediri. Meanwhile, product diversity and product quality also have a significant effect on customer loyalty at Mata Hati Cafe Kediri.